2014
DOI: 10.1002/eji.201444602
|View full text |Cite
|
Sign up to set email alerts
|

T/B‐cell interactions are more transient in response to weak stimuli in SLE‐prone mice

Abstract: Changes in immune function during the course of systemic lupus erythematosus (SLE) are well characterized. Class-switched antinuclear antibodies are the hallmark of SLE, and T/B- cell interactions are thus critical. However, changes in immune function contributing to disease susceptibility are unknown. Here, we have analyzed primary T and B cells from a mouse model of SLE prior to the onset of disease. To allow cognate T-cell activation with low affinity, we have developed a lower potency peptide ligand for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Recently, Sinai et al also have reported altered B and T cell interactions to be responsible for increased GC B cell phenotype in vitro in autoimmune prone B6. Sle1 mice (31). …”
Section: Discussionmentioning
confidence: 99%
“…Recently, Sinai et al also have reported altered B and T cell interactions to be responsible for increased GC B cell phenotype in vitro in autoimmune prone B6. Sle1 mice (31). …”
Section: Discussionmentioning
confidence: 99%
“…SLE patients show aberrant and increased expression of recombination-activating genes (RAG) in peripheral B cells, which can lead to mutation of BCR and thus development of autoreactive B lymphocytes [26]. Aberrant T cell-B cell interaction (e.g., shorted interaction time in the germinal center) results in inadequate anergic signals to autoreactive B cells and hence enhancing their survival [27,28]. Increased BCR-mediated signaling can also lower the activation threshold of peripheral B lymphocytes and promote cellular phenotypes characteristic of SLE [29].…”
Section: Abnormalities In B Cell Tolerance and Regulation-role In Slementioning
confidence: 99%
“…This is despite their having normal central tolerance processes in the bone marrow . In the Sle1 murine model, disease risk is inherited via a region on chromosome 1, carrying polymorphisms in genes encoding multiple receptors needed for T cell–B cell interactions (including Slam , Ly108 , Cd84 , Cracc , and Ly9 ) . In the germinal centers (GCs) of these mice, transient short‐term contact between B cells and T cells allows rare autoreactive B cells and T cells to “sample” many different cells in the GC, increasing chances of interaction for positive costimulation .…”
Section: Checkpoint At B Cell Maturation In the Lymphoid Tissue Frommentioning
confidence: 99%
“…In the Sle1 murine model, disease risk is inherited via a region on chromosome 1, carrying polymorphisms in genes encoding multiple receptors needed for T cell–B cell interactions (including Slam , Ly108 , Cd84 , Cracc , and Ly9 ) . In the germinal centers (GCs) of these mice, transient short‐term contact between B cells and T cells allows rare autoreactive B cells and T cells to “sample” many different cells in the GC, increasing chances of interaction for positive costimulation . Shorter contact times between immune cells are also known to alter their function (e.g., poorer Treg cell ability to induce tolerance in target cells due to shorter contact times) .…”
Section: Checkpoint At B Cell Maturation In the Lymphoid Tissue Frommentioning
confidence: 99%